Challenges and Strategies to the Total Syntheses of Fawcettimine-Type and Serratinine-Type Lycopodium Alkaloids - Wang, Xiaoming; Li, Houhua; Lei, Xiaoguang (Synlett, 2013)
The fawcettimine- and serratinine-type lycopodium alkaloids are a series of structurally complex but related natural products. These alkaloids have been the subjects of intense studies by the synthetic chemistry community, and many elegant strategies have been developed. Herein, we describe the recently disclosed synthetic strategies towards this unique family of natural products, in particular the synthetic endeavors from our research laboratory.
Keywords: total synthesis; fawcettimine; serratinine; lycopodium alkaloid; biosynthesis; collective synthesis; ring-chain tautomerism